DOI: 10.1007/978-3-540-85565-1_105
|View full text |Cite
|
Sign up to set email alerts
|

Aware Group Home Enhanced by RFID Technology

Abstract: Abstract. In Japan, a Group Home which offers home-based care service for elderly persons who suffer from dementia have been increased. Even though the small community of the home is suitable for familylike care, the short of caregivers increases the burden especially during midnight. To supplement the lack of attention, we developed floor mats embedded with RFID antenna and slippers with RFID tags. The system can help the caregivers to aware activities of the persons with dementia by specifying whether the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Currently, there are many researches regarding the "Digital Home", which include providing health care for seniors [6][7][8][9], they focus on the issues of daily activity tracking [6,7] to avoid accidents or irregular activities and reminders for the seniors by identities [8,9], ex: scheduling for activities and medication, eating/drinking instructions.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, there are many researches regarding the "Digital Home", which include providing health care for seniors [6][7][8][9], they focus on the issues of daily activity tracking [6,7] to avoid accidents or irregular activities and reminders for the seniors by identities [8,9], ex: scheduling for activities and medication, eating/drinking instructions.…”
Section: Related Workmentioning
confidence: 99%
“…Miura et al [40] discussed technology for tracking movements of individuals in residential care using 'tagged' slippers and piezoelectric pressure mats. The authors indicated that for safety, pressure mats can only be placed below carpets.…”
Section: Wanderingmentioning
confidence: 99%
“…After considering the requirements and limitations, we chose a simple radio frequency identification (RFID) technology to detect personal activities of elderly persons by embedding tags in their slippers [4]. Our system employs special floor mats with embedded RFID readers that can detect a person's approach to the mat and store the information.…”
Section: System Requirements and Designmentioning
confidence: 99%